Higher Brain Uptake of Gentamicin and Ceftazidime under Isoflurane Anesthesia Compared to Ketamine/Xylazine - Yeseul Ahn; Chanakya D. Patil; Ehsan Nozohouri; Sumaih Zoubi; Dhavalkumar Patel; Ulrich Bickel (MDPI AG, 2024)
We have recently shown that the volatile anesthetics isoflurane and sevoflurane acutely enhance the brain uptake of the hydrophilic markers sucrose and mannitol about two-fold from an awake condition, while the combined injection of the anesthetic agents ketamine and xylazine has no effect. The present study investigated two small-molecule hydrophilic drugs with potential neurotoxicity, the antibiotic agents ceftazidime and gentamicin. Transport studies using an in vitro blood-brain barrier (BBB) model, a monolayer of induced pluripotent stem cell-derived human brain microvascular endothelial cells seeded on Transwells, and LC-MS/MS analysis demonstrated the low permeability of both drugs in the range of sucrose, with permeability coefficients of 6.62 × 10−7 ± 2.34 × 10−7 cm/s for ceftazidime and 7.38 × 10−7 ± 2.29 × 10−7 cm/s for gentamicin. In vivo brain uptake studies of ceftazidime or gentamicin after IV doses of 25 mg/kg were performed in groups of 5-6 mice anesthetized at typical doses for surgical procedures with either isoflurane (1.5-2% v/v) or ketamine/xylazine (100:10 mg/kg I.P.). The brain uptake clearance, Kin, for ceftazidime increased from 0.033 ± 0.003 μL min−1 g−1 in the ketamine/xylazine group to 0.057 ± 0.006 μL min−1 g−1 in the isoflurane group (p = 0.0001), and from 0.052 ± 0.016 μL min−1 g−1 to 0.101 ± 0.034 μL min−1 g−1 (p = 0.0005) for gentamicin. We did not test the dose dependency of the uptake, because neither ceftazidime nor gentamicin are known substrates of any active uptake or efflux transporters at the BBB. In conclusion, the present study extends our previous findings with permeability markers and suggests that inhalational anesthetic isoflurane increases the BBB permeability of hydrophilic small-molecule endobiotics or xenobiotics when compared to the injection of ketamine/xylazine. This may be of clinical relevance in the case of potential neurotoxic substances.